Level of Tourism Development in Uzbekistan at the Recent Stage - Sh. I Xabibova; F.SH Usmanov (Universitas Muhammadiyah Sidoarjo, 2020)
This article is devoted to the modern development of tourism and their types. Considered the volumes of international tourist arrivals and departures of local citizens for 2019 in the Republic of Uzbekistan . Outlined the ways of solving the problems of the tourism sector in Uzbekistan .